Human-centered algorithmic composition for well-being music - Gonçalves Junior, Clenio B.; Neris, Vânia Paula de Almeida (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2023: Anais do XXIII Simpósio Brasileiro de Computação Aplicada à SaúdeDO - 10.5753/sbcas.2023.229409, 2023)
The use of music to bring about health benefits is a well-established practice the outcomes of which have been confirmed by research in recent years. By leveraging this capability, the algorithmic composition aimed at producing specific effects on the listener has become a growing field for the automatic creation of well-being music. This work makes a contribution to this field, through a documentary investigative study that puts forward a comprehensive set of human-centered features that should be included in the algorithmic composition of music for well-being. The results are based on a systematic review of 60 papers published in the last few years. The set is divided into categories as a means of assisting their use by the teams involved.